An artificial immune system-based algorithm to solve linear and loop layout problems in flexible manufacturing systems. (4th December 2009) - Satheesh Kumar, R.M.; Asokan, P.; Kumanan, S.
The Facility Layout Problem (FLP) is concerned with the arrangement of facilities in a given location and is one of the well-explored problems in the field of combinatorial optimisation. Both linear and loop layouts are widely preferred configurations in Flexible Manufacturing Systems (FMSs) because of their materials handling flexibility and agility in accommodating new parts and processes. This paper considers both single-row and loop layout problems in FMSs. The problem is modelled as a Quadratic Assignment Problem (QAP). The Artificial Immune System (AIS) algorithm is employed to solve this problem. The effectiveness of the AIS algorithm is tested and validated through benchmarking problems. The results show that the AIS approach performs well in all test problems. In addition, the single-row and loop layout problems are compared based on the objective of minimising the materials handling cost.